2018
DOI: 10.1038/s41598-018-34335-5
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Chemistry of Non-Enzymatic Browning Reactions in Different Ribose-Amino Acid Model Systems

Abstract: Reactions between sugars and amino acids in the Maillard reaction produce a multitude of compounds through interconnected chemical pathways. The course of the pathways changes depending on the nature of the amino acids and sugars as well as the processing conditions (e.g. temperature, water activity). Some partial pathways have been elucidated using labelled precursors but the process is very time intensive. Here, we use rapid, non-targeted analysis with Fourier transform ion cyclotron resonance mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 44 publications
(46 reference statements)
1
70
0
Order By: Relevance
“…To identify the products formed during the MR, Hemmler et al (2018) recently used a non-targeted analysis with Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS) to derive the molecular formulae of compounds formed after 10 h of heating at 100 • C for different sugar-amino acid combinations [132]. The reaction rate order that was found for amino acids was: Lysine > cysteine > isoleucine ≈ glycine.…”
Section: Factors Influencing the Mrmentioning
confidence: 99%
“…To identify the products formed during the MR, Hemmler et al (2018) recently used a non-targeted analysis with Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS) to derive the molecular formulae of compounds formed after 10 h of heating at 100 • C for different sugar-amino acid combinations [132]. The reaction rate order that was found for amino acids was: Lysine > cysteine > isoleucine ≈ glycine.…”
Section: Factors Influencing the Mrmentioning
confidence: 99%
“…One another reason may be the amino acid residues contained in whey, which is a rich source of the essential amino acids such as lysine, methionine, threonine, and histidine (Gorissen et al., 2018). In many studies investigating the nonenzymatic browning reactions in model systems, it was shown that the lysine is the most reactive amino acid (Ajandouz & Puigserver, 1999; Ashoor & Zent, 1984; Hemmler et al., 2018). Shen, Tebben, Chen, and Li (2018) studied on the effects of different amino acids on bread properties and reported that breads with darker and less yellowish crust colors were obtained with the addition of amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…A second mechanism for the formation of endogenous AGEs in the GI tract could therefore be the presence of fructose in the ginger biscuit, which is highly reactive in the Maillard reaction due to its reduced stability of the ring structure compared to glucose. 32 Although conflicting evidence exists on whether there is a correlation between dAGE uptake and AGE serum and urine levels, a perspective by DeChristopher published in 2017 proposed that a source for increased serum AGE levels may be the formation of AGEs in the GI tract. 33 Fructose is actively absorbed in the human GI tract together with glucose in a 1 : 1 ratio.…”
Section: Gastricmentioning
confidence: 99%